Alkyl ether sulfate surfactants and related methods of manufacture

By preparing a composition with specific alcohol ethoxylates and sulfated surfactants, the problem of AES surfactants forming high concentrations of dioxane under sulfated and high temperature conditions is solved, and the effect of low dioxane concentration and high thermal stability is achieved.

CN119866327APending Publication Date: 2025-04-22DOW GLOBAL TECHNOLOGIES LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380064394.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-09-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing alkyl ethoxysulfate (AES) surfactants are prone to form 1,4-dioxane higher than the regulations during sulfation and high temperature treatment, resulting in the dioxane content in the product exceeding the standard, and the traditional stripping technology is expensive and time-consuming, making it difficult to effectively control the dioxane concentration.

Method used

By preparing an alcohol ethoxylate and a sulfated surfactant that limits the content of oligomers with ethylene oxide (EO) numbers of 2 or more at high temperatures up to 280°C, ensuring that 95 mol % or more of the surfactant has a single ethylene oxide unit and that 5 mol % or less of the surfactant has an ethylene oxide content of 2 or more.

Benefits of technology

It is achieved that 9ppm or more of 1,4-dioxane is not formed under sulfation and high temperature conditions, which reduces the concentration of dioxane in the product, avoids the problem of dioxane formation over time in traditional technology, and improves the thermal stability and regulatory compliance of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005300961720000041
    Figure BDA0005300961720000041
  • Figure BDA0005300961720000051
    Figure BDA0005300961720000051
  • Figure BDA0005300961720000131
    Figure BDA0005300961720000131
Patent Text Reader

Abstract

A process comprises the steps of contacting an olefin, an alcohol, and a metal silicate catalyst to form an oligomer of an alcohol ethoxylate having the structure (I) wherein R1 is an alkyl group, R2 is an alkyl group, and n has a value from 1 to 3; and sulfating the oligomer of structure (I) to form an oligomer of structure (II) wherein R1 is alkyl, R2 is selected from the group consisting of alkyl groups, M is selected from the group consisting of protons, ammonium cations, metal cations, nitrogen cations, boron cations, phosphorus cations, triethylamine, triethanolamine, monoethanolamine, and combinations thereof, and n has a value of 1 to 3, and wherein n is 1 in 95 mol% or more of the oligomer of structure (II) and n is 2 or more in 5 mol% or less of the oligomer of structure (II).
Need to check novelty before this filing date? Find Prior Art

Description

Background Art Technical Field

[0001] The present disclosure relates generally to surfactants, and more particularly to alkyl ether sulfate surfactants and related methods of making.

[0002] introduction

[0003] Regulatory agencies have been tightening limits on the amount of 1,4-dioxane ("dioxane") that may be present in consumer products. For example, New York State already allows only trace amounts of dioxane in cosmetics, personal care products, and cleaning products. Generally, dioxane levels in consumer products must be less than 10 parts per million ("ppm") to comply with the regulations. One source of dioxane in consumer products can be alkyl ethoxy sulfate ("AES") anionic surfactants.

[0004] It is believed that AES surfactants form dioxane at multiple points in time. The first point in time for the formation of dioxane in AES surfactants occurs during the sulfation process of alcohol ethoxylates, which is used to make alcohol ethoxysulfates. The alcohol ethoxylate intermediates used to produce alcohol ethoxysulfate surfactants are prepared by an ethoxylation reaction (i.e., the reaction of an alcohol with ethylene oxide), which typically results in an oligomeric distribution of alcohol ethoxylates. It is believed that dioxane can be formed under the conditions of the sulfation process.

[0005] The second point of dioxane formation in AES surfactants occurs during handling and processing. The handling and processing of sulfated surfactants typically involves acidic conditions at ambient or elevated temperatures. Prolonged exposure of AES surfactants and their alcohol ethoxylate precursors to acidic environments can lead to the formation of dioxane. In addition, exposure to elevated temperatures during processing (e.g., 280°C), storage, and handling can cause AES surfactants to decompose, leading to the formation of dioxane. Therefore, AES surfactants that exhibit thermal stability will reduce the concentration of dioxane in the product.

[0006] Traditionally, dioxane levels in sulfated surfactants and products incorporating such surfactants have been addressed through the use of stripping techniques. For example, when dioxane concentrations are above a target threshold, a stripping process is used to remove excess dioxane from the sulfated surfactant or products incorporating such surfactants. Stripping processes are expensive and time consuming. Furthermore, since dioxanes may form over time depending on how the surfactant or product is handled and further processed, any stripping techniques previously employed may be rendered ineffective by the generation of new dioxanes. Therefore, it is a daunting challenge to ensure that products made from sulfated surfactants comply with relevant regulations when sold to the end consumer.

[0007] In view of the foregoing, it would be surprising and advantageous to discover an alcohol ethoxylate and sulfated surfactant that does not form 9 ppm or more of dioxane upon sulfation and exposure to elevated temperatures up to 280°C. Summary of the invention

[0008] The inventors of the present application have discovered an alcohol ethoxylate and sulfated surfactant that does not form 9 ppm or more of dioxane upon sulfation and exposure to elevated temperatures up to 280°C.

[0009] The inventors of the present disclosure have discovered that the above-described properties can be achieved with surfactant compositions wherein 95 mole percent ("mol %) or more of the surfactant has a single ethylene oxide unit and 5 mol % or less of the surfactant has an ethylene oxide content of 2 or more. Without being bound by theory, it is believed that the distribution of oligomers produced during the alkoxylation process is responsible for the formation of dioxanes in alcohol ethoxylates and sulfated surfactants. It is believed that oligomers having an ethylene oxide ("EO") number of 2 or more can undergo a "backbite" reaction to produce undesirable dioxanes. Surprisingly, by limiting the content of oligomers having 2 EO units to 5 mol % or less, the surfactants do not produce 9 ppm of dioxanes during sulfation and when exposed to 280°C. In addition, it has been discovered that contacting an alcohol and an olefin in the presence of a metal silicate catalyst can produce the above-described alcohol ethoxylates.

[0010] The present invention is particularly useful in forming AES surfactants and products made therefrom.

[0011] According to a first feature of the present disclosure, a method comprises the steps of contacting an olefin, an alcohol and a metal silicate catalyst to form an alcohol ethoxylate oligomer having structure (I), wherein R 1 is an alkyl group, R 2 is an alkyl group, and n has a value of 1 to 3; and sulfating an oligomer of structure (I) to form an oligomer of structure (II), wherein R 1 is an alkyl group, R 2 Selected from the group consisting of alkyl groups, M is selected from the group consisting of: protons, ammonium cations, metal cations, nitrogen cations, boron cations, phosphorus cations, triethylamine, triethanolamine, monoethanolamine and combinations thereof, and the value of n is 1 to 3, and wherein 95 mol% or more of the oligomers of structure (II) have n of 1, and 5 mol% or less of the oligomers of structure (II) have n of 2 or greater.

[0012] According to the second feature of the present disclosure, the olefin is C 8 To C 18 An alpha olefin is present, and the alcohol is monoethylene glycol.

[0013] According to the third feature of the present disclosure, R 1 and R 2 The total number of carbon atoms in the molecule is between 7 and 17.

[0014] According to the fourth feature of the present disclosure, R 1 and R 2 The total number of carbon atoms in the carbon is 11 to 13.

[0015] According to the fifth feature of the present disclosure, the surface area of ​​the catalyst used to prepare structure (I) is 680 m 2 / g.

[0016] According to the sixth feature of the present disclosure, n is 1 in 98 mol % or more of the oligomers of the structure (I), and n is 2 or more in 2 mol % or less of the oligomers of the structure (I).

[0017] According to the seventh feature of the present disclosure, the surfactant composition comprises an oligomer of a surfactant having structure (II), wherein R 1 is an alkyl group, R 2 is an alkyl group, M is selected from the group consisting of a proton, an ammonium cation, a metal cation, a nitrogen cation, a boron cation, a phosphorus cation, triethylamine, triethanolamine, monoethanolamine, and combinations thereof, and n has a value of 1 to 3, and wherein 95 mol % or more of the oligomers of structure (II) in the composition have n of 1, and 5 mol % or less of the oligomers of structure (II) in the composition have n of 2 or greater.

[0018] According to the eighth feature of the present disclosure, R of structure (II) 1 C 1 To C 16 Alkyl, R 2 Choose from C 1 To C 16 alkyl, wherein R 1 and R 2 The total number of carbon atoms in the molecule is between 7 and 17.

[0019] According to the ninth feature of the present disclosure, n is 1 in 98 mol% or more of the oligomers of structure (II) in the surfactant composition, and n is 2 or greater in 2 mol% or less of the oligomers of structure (II) in the surfactant composition.

[0020] According to the tenth feature of the present disclosure, R 1 and R 2 The total number of carbon atoms in the carbon is 11 to 13.

[0021] According to an eleventh feature of the present disclosure, a material includes 0.1 wt % to 99.9 wt % of a surfactant composition. DETAILED DESCRIPTION

[0022] As used herein, the term "and / or," when used in a list of two or more items, means that any one of the listed items may be used alone, or any combination of two or more of the listed items may be used. For example, if a composition is described as containing components A, B, and / or C, the composition may contain A alone; B alone; C alone; A and B in combination; A and C in combination; B and C in combination; or A, B, and C in combination.

[0023] Unless otherwise stated, all ranges are inclusive.

[0024] Test methods refer to the most recent test methods as of the priority date of this document, unless the date is expressed as a two-digit number with a hyphen in the test method number. Reference to a test method includes reference to both the testing association and the test method number. Test method organizations are referenced by one of the following abbreviations: ASTM refers to ASTM International (formerly the American Society for Testing and Materials); EN refers to European Standards; DIN refers to the German Institute for Standardization; and ISO refers to the International Organization for Standardization.

[0025] Unless otherwise indicated, the IUPAC codes describing crystal structures as described by the Structure Commission of the International Zeolite Association refer to the most recent names as of the priority date of this document.

[0026] As used herein, the term weight percent ("wt %") represents the weight percent of a component based on the total weight of the indicated composition.

[0027] Alcohol ethoxylate

[0028] The present disclosure provides alcohol ethoxylates having structure (I):

[0029]

[0030] Where R 1 is an alkyl group, R 2 is selected from the group consisting of alkyl groups, and the value of n is 1 to 3. 1 The alkyl group may have 1 carbon atom (i.e., C 1 Alkyl) to 16 carbon atoms (i.e., C 16 For example, R 1 Can be C 1 Alkyl, or C2 Alkyl, or C 3 Alkyl, or C 4 Alkyl, or C 5 Alkyl, or C 6 Alkyl, or C 7 Alkyl, or C 8 Alkyl, or C 9 Alkyl, or C 10 Alkyl, or C 11 Alkyl, or C 12 Alkyl, or C 13 Alkyl, or C 14 Alkyl, or C 15 Alkyl, or C 16 Alkyl. 1 The alkyl group may be saturated or unsaturated. 2 The alkyl group can be C 1 To C 16 Alkyl. For example, R 2 Can be C 1 Alkyl, or C 2 Alkyl, or C 3 Alkyl, or C 4 Alkyl, or C 5 Alkyl, or C 6 Alkyl, or C 7 Alkyl, or C 8 Alkyl, or C 9 Alkyl, or C 10 Alkyl, or C 11 Alkyl, or C 12 Alkyl, or C 13 Alkyl, or C 14 Alkyl, or C 15 Alkyl, or C 16 Alkyl. 2 The alkyl group present in R 1 and R 2 The total number of carbon atoms in is 7 to 17. For example, 1 and R 2 The sum of carbon atoms in the R can be 7 or more, or 8 or more, or 9 or more, or 10 or more, or 11 or more, or 12 or more, or 13 or more, or 14 or more, or 15 or more, or 16 or more, and at the same time, 17 or less, or 16 or less, or 15 or less, or 14 or less, or 13 or less, or 12 or less, or 11 or less, or 10 or less, or 9 or less, or 8 or less. The value of n in Structure (I) is 1 to 3. For example, n can be 1, 2 or 3. The presence of R 1 and R 2 The carbon number and n value in are all based on the following 13C NMR characterization.

[0031] Due to the process used in forming the alcohol ethoxylates of structure (I) which results in a natural distribution of products, the values ​​of n may vary among the oligomers of structure (I). For example, the composition of oligomers of structure (I) may have the same R 1 and R 2 , but with different n values ​​of 1, 2 and 3. In general, 95 mol% or more of the oligomers of structure (I) have n of 1, and 5 mol% or less of the oligomers of structure (I) have n of 2 or greater. For example, according to the following 13 C NMR characterization, 95.0 mol% or more, or 95.5 mol% or more, or 96.0 mol% or more, or 96.5 mol% or more, or 97.0 mol% or more, or 97.5 mol% or more, or 98.0 mol% or more, or 98.5 mol% or more, or 99.0 mol% or more, or 99.5 mol% or more, while at the same time, 100.0 mol% or less, or 99.5 mol% or less, or 99.0 mol% or less, or 98.5 mol% or less, or 98.0 mol% or less, or 97.5 mol% or less, or 97.0 mol% or less, or 96.5 mol% or less, or 96.0 mol% or less, or 95.5 mol% or less of the oligomers of structure (I) have an n value of 1. In addition, as provided below 13 C NMR characterization, 5.0 mol% or less, or 4.5 mol% or less, or 4.0 mol% or less, or 3.5 mol% or less, or 3.0 mol% or less, or 2.5 mol% or less, or 2.0 mol% or less, or 1.5 mol% or less, or 1.0 mol% or less, or 0.5 mol% or less, while at the same time, 0.0 mol% or more, or 0.5 mol% or more, or 1.0 mol% or more, or 1.5 mol% or more, or 2.0 mol% or more, or 2.5 mol% or more, or 3.0 mol% or more, or 3.5 mol% or more, or 4.0 mol% or more, or 4.5 mol% or more of the oligomers of structure (I) have an n value of 2 or greater.

[0032] Surfactant composition

[0033] The present disclosure also relates to a surfactant composition. The surfactant composition comprises an oligomer of a surfactant having structure (II):

[0034]

[0035] Where R1 is an alkyl group, and R 2 is an alkyl group. 1 The alkyl group can be C 1 To C 16 Alkyl. For example, R 1 Can be C 1 Alkyl, or C 2 Alkyl, or C 3 Alkyl, or C 4 Alkyl, or C 5 Alkyl, or C 6 Alkyl, or C 7 Alkyl, or C 8 Alkyl, or C 9 Alkyl, or C 10 Alkyl, or C 11 Alkyl, or C 12 Alkyl, or C 13 Alkyl, or C 14 Alkyl, or C 15 Alkyl, or C 16 Alkyl. 1 The alkyl group may be saturated or unsaturated. 2 The alkyl group can be C 1 To C 16 Alkyl. For example, R 2 Can be C 1 Alkyl, or C 2 Alkyl, or C 3 Alkyl, or C 4 Alkyl, or C 5 Alkyl, or C 6 Alkyl, or C 7 Alkyl, or C 8 Alkyl, or C 9 Alkyl, or C 10 Alkyl, or C 11 Alkyl, or C 12 Alkyl, or C 13 Alkyl, or C 14 Alkyl, or C 15 Alkyl, or C 16 Alkyl. 2 The alkyl group present in R 1 and R 2 The total number of carbon atoms in is 7 to 17. For example, 1 and R 2The sum of carbon atoms in the structure (II) can be 7 or more, or 8 or more, or 9 or more, or 10 or more, or 11 or more, or 12 or more, or 13 or more, or 14 or more, or 15 or more, or 16 or more, and at the same time, 17 or less, or 16 or less, or 15 or less, or 14 or less, or 13 or less, or 12 or less, or 11 or less, or 10 or less, or 9 or less, or 8 or less. In a specific example, R of structure (II) 1 and R 2 The total number of carbon atoms in R is 11 to 13. The value of n in structure (II) is 1 to 3. For example, n can be 1, 2 or 3. 1 and R 2 The carbon number and n value in are all based on the following 13 C nuclear magnetic resonance ("NMR") characterization.

[0036] M of structure (II) is selected from the group consisting of: a proton, an ammonium cation, a metal cation, a nitrogen cation, a boron cation, a phosphonium cation, triethylamine, triethanolamine, monoethanolamine, and combinations thereof. It should be understood that different surfactant molecules may have different materials for M.

[0037] As with structure (I), the value of n of structure (II) may vary. In the surfactant composition, 95 mol% or more of the oligomers of structure (II) have n of 1, and 5 mol% or less of the oligomers of structure (II) have n of 2 or greater. For example, 95.0 mol% or more, or 95.5 mol% or more, or 96.0 mol% or more, or 96.5 mol% or more, or 97.0 mol% or more, or 97.5 mol% or more, or 98.0 mol% or more, or 98.5 mol% or more, or 99.0 mol% or more, or 99.5 mol% or more of the composition, while at the same time, 100.0 mol% or less, or 99.5 mol% or less, or 99.0 mol% or less, or 98.5 mol% or less, or 98.0 mol% or less, or 97.5 mol% or less, or 97.0 mol% or less, or 96.5 mol% or less, or 96.0 mol% or less, or 95.5 mol% or less of the oligomers of structure (II) have an n value of 1. In addition, 5.0 mol% or less, or 4.5 mol% or less, or 4.0 mol% or less, or 3.5 mol% or less, or 3.0 mol% or less, or 2.5 mol% or less, or 2.0 mol% or less, or 1.5 mol% or less, or 1.0 mol% or less, or 0.5 mol% or less, while at the same time, 0.0 mol% or more, or 0.5 mol% or more, or 1.0 mol% or more, or 1.5 mol% or more, or 2.0 mol% or more, or 2.5 mol% or more, or 3.0 mol% or more, or 3.5 mol% or more, or 4.0 mol% or more, or 4.5 mol% or more of the oligomers of structure (II) in the composition have an n value of 2 or greater.

[0038] The surfactant composition may contain 9 ppm or less 1,4-dioxane as measured by the GCMS and LCMS methods described in more detail below. For example, the surfactant composition may contain 9 ppm or less 1,4-dioxane, or 8 ppm or less, or 7 ppm or less, or 6 ppm or less, or 5 ppm or less, or 4 ppm or less, or 3 ppm or less, or 2 ppm or less, or 1 ppm or less. As described above, the relative molar concentrations of oligomers of structures (I) and (II) are such that dioxane formation is not only inhibited during the sulfation process, but also remains so in the presence of heat and over a period of time.

[0039] Material

[0040] The present disclosure also relates to a material comprising a surfactant composition. The material can be a personal care product, a cleaning product, a coating, an emulsion polymerization solution, a textile process additive or composition, an agricultural adjuvant or composition, an oil and gas production additive or composition, an ink, a paper and pulp additive or composition, and other industrial process additives or compositions. The material can contain 0.1 weight percent ("wt %) to 99.9 wt % of the surfactant composition based on the total weight of the material. For example, the material may contain 0.1 wt% or more, or 1.0 wt% or more, or 5.0 wt% or more, or 10 wt% or more, or 20 wt% or more, or 30 wt% or more, or 40 wt% or more, or 50 wt% or more, or 60 wt% or more, or 70 wt% or more, or 80 wt% or more, or 90 wt% or more, or 99 wt% or more, while at the same time, 99.9 wt% or less, or 99 wt% or less, or 90 wt% or less, or 80 wt% or less, or 70 wt% or less, or 60 wt% or less, or 50 wt% or less, or 40 wt% or less, or 30 wt% or less, or 20 wt% or less, or 10 wt% or less, or 5 wt% or less, or 1.0 wt% or less of the surfactant composition, based on the total weight of the material. Similar to the surfactant composition, the 1,4-dioxane content of this material was 9 ppm or less as measured according to the headspace gas chromatography flame ionization detection method described in more detail below.

[0041] method

[0042] The present disclosure also relates to a method. The method comprises the steps of contacting an olefin, an alcohol, and a metal silicate catalyst to form an oligomer of an alcohol ethoxylate having structure (I).

[0043] An olefin, an alcohol, a metal silicate catalyst and a solvent are contacted to produce an alcohol ethoxylate having structure (I). The chemical reaction between the olefin and the alcohol is catalyzed by the metal silicate catalyst in the reactor to produce an alcohol ethoxylate having structure (I).

[0044] The reaction of olefins and alcohols can be carried out at a temperature of 50°C to 300°C or 100°C to 200°C. In a specific example, the reaction can be carried out at 135°C. The reaction of olefins and alcohols can be carried out in a batch reactor, a continuous reactor or a fixed bed reactor. In the operation of the chemical reaction, the Bronsted acid sites of the metal silicate catalyst catalyze the etherification of olefins to alcohols through an addition-type reaction. The reaction of olefins and alcohols produces an alcohol ethoxylate having structure (I).

[0045] Olefins

[0046] The olefin used in the process may be linear, branched, acyclic, cyclic or a mixture thereof. The olefin may be C 8 To C 18 Olefins. Olefins can be C 8 Olefins, or C 9 Olefins, or C 10 Olefins, or C 11 Olefins, or C 12 Olefins, or C 13 Olefins, or C 14 Olefins, or C 15 Olefins, or C 16 Olefins, or C 17 Olefins, or C 18 Olefins.

[0047] The olefins may include alkenes such as alpha olefins, internally disubstituted olefins, or cyclic structures (e.g., C 8 To C 12 Cyclic olefins). Alpha olefins contain unsaturated bonds in the alpha position of the olefin. Suitable alpha olefins can be selected from the group consisting of 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 1-docosene and combinations thereof. Internal disubstituted olefins contain unsaturated bonds that are not in the terminal position of the olefin. Internal olefins can be selected from the group consisting of 2-octene, 3-octene, 4-octene, 2-nonene, 3-nonene, 4-nonene, 2-decene, 3-decene, 4-decene, 5-decene and combinations thereof. Other exemplary olefins can include butadiene and styrene.

[0048] Examples of suitable commercially available olefins include NEODENE available from Shell, The Hague, Netherlands. TM 8. NEODENE TM 10. NEODENE TM 12. NEODENE TM 14. NEODENE TM 16. NEODENE TM 1214、NEODENE TM 1416. NEODENE TM 16148.

[0049] alcohol

[0050] The alcohol used in the method is an alkylene glycol. The alcohol can be selected from the group consisting of monoethylene glycol, diethylene glycol, propylene glycol, triethylene glycol, polyethylene glycol, monopropylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 2,3-butylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,4-cyclohexane methanediol, glycerol and / or combinations thereof. According to various examples, the alcohol is a (poly) alkylene glycol such as monoethylene glycol, diethylene glycol, propylene glycol and triethylene glycol.

[0051] The molar ratio of alcohol to olefin in the process can be 20:1 or less, or 15:1 or less, or 10:1 or less, or 9:1 or less, or 8:1 or less, or 7:1 or less, or 6:1 or less, or 5:1 or less, or 4:1 or less, or 3:1 or less, or 2:1 or less, or 0.2:1 or less, while at the same time, 0.1:1 or greater, or 1:1 or greater, or 1:2 or greater, or 1:3 or greater, or 1:4 or greater, or 1:5 or greater, or 1:6 or greater, or 1:7 or greater, or 1:8 or greater, or 1:9 or greater, or 1:10 or greater, or 1:15 or greater, or 1:20 or greater.

[0052] Metal silicate catalyst

[0053] As used herein, the term "metal silicate catalyst" is an aluminosilicate (commonly referred to as a zeolite) compound having a crystal lattice in which one or more metal elements have been replaced by silicon atoms. The crystal lattice of the metal silicate catalyst forms cavities and channels in the interior in which cations, water and / or small molecules can reside. The substituting metal element may include one or more metals selected from the group consisting of: B, Al, Ga, In, Ge, Sn, P, As, Sb, Sc, Y, La, Ti, Zr, V, Cr, Mn, Pb, Pd, Pt, Au, Fe, Co, Ni, Cu, Zn. The metal silicate catalyst may be substantially free of Hf. According to various embodiments, the ratio of silicon dioxide to aluminum oxide of the metal silicate may be 5: 1 to 1,500: 1 as measured using neutron activation analysis. The ratio of silica to alumina can be from 5: 1 to 1,500: 1, or from 10: 1 to 500: 1, or from 10: 1 to 400: 1, or from 10: 1 to 300: 1, or from 10: 1 to 200: 1. Such a ratio of silica to alumina can be advantageous in providing a highly homogeneous metal silicate catalyst having organophilic-hydrophobic selectivity for adsorbing non-polar organic molecules.

[0054] The metal silicate catalyst may have one or more ion-exchangeable cations outside the crystal lattice. The ion-exchangeable cations may include H + , Li + 、Na+ , Rb + , Cs + Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ Sc 3+ , Y 3+ ,La 3+ , R 4 N + , R 4 P + (wherein R is H or alkyl).

[0055] The metal silicate catalyst can have a variety of crystal structures. Specific examples of metal silicate catalyst structures include MFI (e.g., ZSM-5), MEL (e.g., ZSM-11), BEA (e.g., β-type zeolite), FAU (e.g., Y-type zeolite), MOR (e.g., mordenite), MTW (e.g., ZSM-12) and LTL (e.g., Linde L), as described using the IUPAC code according to the nomenclature of the International Zeolite Association Structure Committee.

[0056] The crystalline framework of metal silicate catalysts consists of molecular-sized channels and corner-sharing tetrahedra [TO 4 ] (T = Si or Al) mainly constructs the network representation of the cage composed of the block. Negative charge can be introduced into the framework through isomorphous substitution of tetravalent silicon of the framework by trivalent metal (e.g., aluminum) atoms. The overall charge neutrality is then achieved by introducing cationic species that compensate for the resulting negative lattice charge. When oil protons provide such charge compensation, Bronsted acid sites are formed, making the resulting H-type zeolite a strong solid Bronsted acid.

[0057] The metal silicate catalyst can be used in the method in a variety of forms. For example, the metal silicate catalyst can be a powder (e.g., particles having a longest linear dimension of less than 100 microns), a granular (e.g., particles having a longest linear dimension of 100 microns or greater), or a molded article of a powdered and / or granular metal silicate catalyst.

[0058] The surface area of ​​a metal silicate catalyst can be 100 m 2 / g or more, or 200m 2 / g or more, or 300m 2 / g or more, or 400m 2 / g or more, or 500m 2 / g or more, or 600m 2 / g or more, or 700m 2 / g or more, or 800m 2 / g or greater, or 900m 2 / g or more, and at the same time 1000m 2 / g or less, or 900m 2 / g or less, or 800m 2 / g or less, or 700m 2 / g or less, or 600m 2 / g or less, or 500m 2 / g or less, or 400m 2 / g or less, or 300m 2 / g or less, or 200m 2 / g or less. The surface area is measured according to ASTM D4365-19.

[0059] The metal silicate catalyst can be synthesized by a hydrothermal synthesis method. For example, the metal silicate catalyst can be synthesized by heating a composition comprising a silica source (e.g., silica sol, silica gel and alkoxysilane), a metal source (e.g., metal sulfate, metal oxide, metal halide, etc.) and a quaternary ammonium salt such as tetraethylammonium salt or tetrapropylammonium to a temperature of about 100° C. to about 175° C. until a crystalline solid is formed. The resulting crystalline solid is then filtered out, washed with water, and dried, and then calcined at a temperature of 350° C. to 600° C.

[0060] Examples of suitable commercially available metal silicate catalysts include CP814E, CP814C, CP811C-300, CBV 712, CBV 720, CBV 760, CBV 2314, CBV 10A, available from ZEOLYST INTERNATIONAL of Conshohocken, Pennsylvania. TM .

[0061] Sulfation

[0062] After the oligomer of structure (I) is formed, the following step is performed: sulfation of the oligomer of structure (I) to form an oligomer of structure (II). Sulfation of the alcohol ethoxylate having structure (I) can be achieved by contacting the alcohol ethoxylate with a sulfating agent capable of sulfating the alcohol, which can be carried out using known methods, such as those described in references (David W. Roberts, "Sulfonation Technologies for Anionic Surfactant Manufacture", Organic Process Research & Development, 1998, Vol. 2, pp. 194-202; Xavier Domingo, "Alcohol and Alcohol Ether Sulfates", included in Anionic Surfactants (Organic Chemistry), Surfactant Science Series Vol. 56 (Edited by Helmut W. Stache), Marcel Dekker, Inc., New York, 1996). Useful sulfating agents include chlorosulfonic acid, sulfuric acid, sulfur trioxide, and aminosulfonic acid. When chlorosulfonic acid is used as the sulfating agent, the sulfation is carried out at a temperature of -10°C to 10°C and a pressure of 0.01 megapascal ("MPa") to 1 MPa. The sulfating agent can be added in a metered amount or mixed with the alcohol ethoxylate all at once. Once the sulfation of the alcohol ethoxylate reaches the desired level, a base (e.g., NaOH, KOH, or NH 4 OH) to neutralize sulfate or sulfate-containing compounds and terminate the sulfation reaction.

[0063] Example

[0064] Material

[0065] The catalyst is a metal silicate catalyst defined by the BEA structure and has a silica to alumina ratio of 25:1 and a 680 m 2 / g surface area, which is available as CP814E from ZEOLYST INTERNATIONAL of Conshohocken, Pennsylvania TM Commercially available.

[0066] 1-Dodecene is an alpha olefin that can be used as a NEODENE TM 12 SHELL from The Hague, Netherlands TM The group purchased it.

[0067] 1-Tetradecene is an alpha olefin that can be used as a NEODENETM 14 SHELL from The Hague, Netherlands TM The group purchased it.

[0068] Monoethylene glycol was purchased from SIGMA ALDRICH TM Liquid anhydrous ethylene glycol, its CAS number is 107-21-1.

[0069] As per 13 ALEO1 is a linear primary alcohol ethoxylate having an average of 1 ethylene oxide unit as measured by C NMR characterization and is available from Huntsman Corporation, The Woodlands, Texas as SURFONIC TM It is commercially available under the trade name SUPERTRAX® L24-1.

[0070] ALEO2 is a 7-molecular straight-chain C 12 To C 15 Primary alcohol ethoxylates, available from Stepan Company, Northfield, Illinois as BIOSOFT TM It is commercially available under the trade name SUPERTRAX® N25-7.

[0071] Sulfuric acid was purchased from SIGMA ALDRICH TM ACS reagent (95% to 98%), its CAS number is 7664-93-9.

[0072] Chlorosulfonic acid was purchased from SIGMA ALDRICH TM The liquid has a CAS number of 7790-94-5.

[0073] Sodium hydroxide (NaOH) was purchased from SIGMA ALDRICH TM A solid with a CAS number of 1310-73-2.

[0074] Dichloromethane (DCM) was purchased from SIGMA ALDRICH TM Liquid anhydrous dichloromethane, its CAS number is 75-09-2.

[0075] SA3EO sulfate is a secondary alcohol ethoxylate with 3 ethylene oxide units, which has been described below with respect to C 12 The basic starting material is a C 12 To C 14 Secondary alcohol ethoxylate, CAS No. 84133-50-6, can be used as TERGITOL TM15-S-3 is commercially available from The Dow Chemical Company, Midland, Michigan.

[0076] Sodium dioctyl sulfosuccinate (SDOSS) BioXtra ≥ 99.0% solid, purchased from SIGMA ALDRICH TM , its CAS number is 577-11-7.

[0077] Sodium dodecyl sulfate (SDS) ≥99.0% (GC) dust-free granules, purchased from SIGMA ALDRICH TM , its CAS number is 151-21-3.

[0078] Hyamine 1622 (benzylethoxyammonium chloride) ≥ 99.0% (AT) is a solid and is available from SIGMA ALDRICH TM , its CAS number is 121-54-0.

[0079] Methylene blue (certified biological stain) is a solid and was purchased from Fischer Scientific TM , its CAS number is 7220-79-3.

[0080] Sodium sulfate anhydrous (granular / certified ACS) was a solid and purchased from Fischer Scientific TM , its CAS number is 7757-82-6.

[0081] Test Method

[0082] Method for determining the percentage of active sulfate content

[0083] This method is improved from the following methods: Turney, ME, Cannell, DW, "Alkalinemethylene blue method for determination of anionic surfactants and for amineoxides in detergents.", J. Am. Oil Chem. Soc., Vol. 42, pp. 544-546 (1965) and Epton, SR, "A new method for the rapid titrimetric analysis of sodium alkylsulphates and related compounds.", Trans. Faraday Soc., Vol. 44, pp. 226-230 (1948).

[0084] 1. Dioctyl Sodium Sulfosuccinate (SDOSS), Control Solution - Charge 0.8 g (± 0.1 mg) of dioctyl sodium sulfosuccinate of known purity (≥ 99%) in a 20 mL scintillation vial. Fill the vial with 10 mL DI water and transfer to a 250 mL volumetric flask. Repeat this process 3 to 5 times to ensure sample transfer. After the transfer is complete, dilute the sample to the mark (250 mL) with DI water. The flask is then stoppered and the solution is thoroughly mixed by repeatedly inverting the flask.

[0085] a. To verify accuracy, a second control solution may be prepared using a similar method as above using sodium dodecyl sulfate (SDS) with a purity of ≥99%. If a second control solution is used, be sure to adjust Equation 1 accordingly.

[0086] b. The purity of the control sample should be >99%. The formula listed below does not take purity into account, so if the purity of the control sample is lower than this standard, it must be taken into account.

[0087] 2. Methylene Blue Chloride Solution - Charge 0.050 g (± 0.005) of methylene blue chloride in a 20 mL scintillation vial. Fill the vial with 10 mL of DI water and transfer to a 1 L graduated cylinder. Repeat this process 3 to 5 times to ensure sample transfer. The methylene blue solution is then diluted to the 1 L mark. This solution is then transferred to a 2 L glass jar. Once the transfer is complete, carefully add 10 mL of concentrated sulfuric acid and 50 g of anhydrous sodium sulfate to the methylene blue solution and mix thoroughly.

[0088] 3. Hyamine 1622 Solution - Place 1.1 grams of Hyamine 1622 in a 20 mL scintillation vial. Fill the vial with 10 mL of DI water and transfer to a 1 L volumetric flask. Repeat this process 3 to 5 times to ensure sample transfer. Then dilute the sample to the 1 L mark with DI water. Mix the solution thoroughly by repeatedly inverting the flask and then filter into a 1 L glass bottle.

[0089] 4. Standardization of Hyamine Solution - Pipette 5 mL of dioctyl sodium sulfosuccinate solution into a 100 mL glass bottle. Next, add 20 mL of methylene blue chloride solution and 25 mL of chloroform via pipette. Cover the 100 mL bottle and shake well for a few seconds. The Hyamine 1622 solution is then titrated into the methylene blue / chloroform biphasic mixture in 0.5 mL increments. After each addition, cover the bottle and shake vigorously. Continue to add Hyamine 1622 in increments of 0.5 mL until the blue color of the chloroform layer (or lower layer) begins to migrate to the upper layer. At this time, reduce the amount of Hyamine 1622 added to 0.1 mL and continue to add until the endpoint is reached. The endpoint is reached when the blue intensity of the two layers is consistent. This standardization is completed in triplicate. The number of moles of Hyamine 1622 is calculated by the following formula :

[0090]

[0091] Mol H = Number of moles of Hyamine

[0092] CS vol = Volume of control solution tested (5 mL)

[0093] CS mass = Total grams of control (SDOSS) added to 250 mL of control solution, accurate to 0.1 mg (g)

[0094] H CSVol = The amount of hyamine solution required to reach the endpoint of the control solution (mL)

[0095] CS MW = molecular weight of the control, SDOSS = 444.56 (g / mol)

[0096] 5. Method for determining the percentage of active sulfate content - 0.9 grams to 1.1 grams of sample are loaded into a 20mL scintillation vial and weighed to the nearest 0.1mg. Fill the vial with 10mL DI water and transfer to a 250mL volumetric flask. This process is repeated 3 to 5 times to ensure sample transfer. After the transfer is complete, dilute the sample to the scale (250mL) with DI water. The flask is then stoppered and the solution is thoroughly mixed by repeatedly inverting the flask. Next, 5mL of the test sample solution is loaded into a 100mL glass bottle via a pipette. Then 20mL of methylene blue solution and 25mL of chloroform are loaded into a 100mL glass bottle via a pipette. Cover the glass bottle and shake vigorously for a few seconds. The Hyamine 1622 solution is then titrated into the methylene blue / chloroform biphasic mixture in 0.5mL increments. After each addition, cover the bottle and shake vigorously.

[0097] Continue to add Hyamine 1622 in 0.5 mL increments until the blue color of the chloroform layer (or lower layer) begins to migrate to the upper layer. At this point, reduce the amount of Hyamine 1622 added to 0.1 mL and continue to add until the endpoint is reached. The endpoint is reached when the color intensity of the two layers is the same. Repeat three times for each sample. Percentage of active sulfate (wt%)

[0098] Determined by the following formula:

[0099]

[0100] H SVol = The amount of Hyamine solution required to reach the endpoint of the test sample solution (mL)

[0101] Mol H = Number of moles of Hyamine (solved in Equation 1)

[0102] S MW = Average MW of the test sample (g / mol)

[0103] S vol = Volume of sample solution tested (5 mL)

[0104] S mass = Total grams of test sample added to 250 mL of solution, accurate to 0.1 mg (g)

[0105] Methods for acid digestion

[0106] 0.5 grams of alcohol ethoxylate material to be tested is loaded into a sample vial. Next, concentrated sulfuric acid (4.0 grams, ACS reagent 95% to 98%) is added to form a reaction solution, and the sample vial is tightly capped. The sample vial is then placed on a heating block and the sample is heated to 90°C. After reaching the set temperature, the reactants are reacted for 1 hour. After completion, the reaction sample vial is taken out and cooled to 23°C. While the sample is cooling, 0.9 grams of 1 molar NaOH aqueous solution is loaded into a separate gas chromatography headspace vial and cooled in an ice bath. After the reaction solution is cooled, 0.1 grams of the reaction solution is added to the pre-cooled gas chromatography headspace vial. Immediately cover the vial and put it back in the ice bath. The sample is then analyzed by headspace gas chromatography with flame ionization detection ("HS-GC / FID") to determine the amount of 1,4-dioxane formed during the digestion process. 1,4-Dioxane will complex with sulfuric acid, so a neutralization step is required to release any 1,4-dioxane produced during the sulfuric acid digestion of the sample.

[0107] Acid digestion analysis

[0108] The neutralized headspace vial was heated at 90°C for 15 minutes to allow 1,4-dioxane to reach concentration equilibrium in the headspace. A 2.5 ml headspace aliquot was extracted using a gas-tight syringe heated at 150°C and subsequently injected into the gas chromatograph. The volatile components in the headspace sample were separated using a Porabond Q column and then detected by a flame ionization detector. The Porabond Q column was used because it is not easily degraded under acidic or alkaline conditions and it provides the best resolution and detection limit for 1,4-dioxane among other acid-degraded sample matrix components. Quantification was performed by external standardization and the detection limit of this method for 1,4-dioxane was found to be 0.1 ppm (w / w).

[0109]

[0110] Liquid injection low temperature GCMS of organic layer

[0111] Standards were prepared by adding a solution of dioxane in tetrahydrofuran ("THF") and diluting to 0.1 ppm to 100 ppm.

[0112] The sample was prepared by mixing 3.3 g of the crude mixture organic (DCM) layer with 6.7 g THF, and then the solution was shaken for about 20 minutes. The solid was then centrifuged to the bottom and the supernatant was placed in an autosampler vial. The spiked samples were prepared by spiking a THF solution of dioxane standards into individual samples at 5 ppm to 10 ppm.

[0113] LCMS of the aqueous layer

[0114]

[0115] Samples were injected neat or diluted 1:4 with water. Standards were prepared by preparing a stock solution of dioxane in THF and diluting with water to 0.1 ppm to 100 ppm.

[0116] Calculation of dioxane content relative to solids

[0117] The ppm value of dioxane content relative to the solid content in the sample was calculated according to Equation 3.

[0118]

[0119] Calculation of EO content

[0120] The weight percent of ethylene oxide content in the sample was calculated according to Equation 2, where MW is the molecular weight in g / mol.

[0121]

[0122] Nuclear Magnetic Resonance ("NMR") Characterization of EO Distribution

[0123] The sample was dissolved in tritiated dimethyl sulfoxide containing 0.025 M chromium (III) acetylacetonate. 13 C NMR spectra were collected on a Bruker AVANCE 400 MHz spectrometer equipped with a 10 mm cryoprobe and set to 25 °C. The spectra were collected with the following parameters: 90° pulse, inverse gated decoupling, 1.38 s acquisition time, and 6.4 s recycle delay. 2048 scans were collected. The data were processed in MNOVA and the chemical shifts were referenced to the solvent peak at 39.52 ppm. The DEPT-135 experiment was also collected with the same parameters, but with a recycle delay of 2.0 s and 2048 scans.

[0124] The ratio of different EO adducts is calculated by accumulating and comparing the ethylene oxide alcohol terminal group intensity of about 60 ppm to 61 ppm, the ethylene oxide main chain group intensity of about 69 ppm to 70 ppm, the ethylene oxide terminal group ether peak intensity of about 71 ppm to 72 ppm, the unreacted primary alcohol peak intensity of about 60 ppm to 61 ppm, and the unreacted secondary alcohol peak intensity of about 65 ppm to 66 ppm.

[0125] Sample preparation

[0126] C 12 Synthesis of EO

[0127] When using the catalyst to etherify 1-dodecene and monoethylene glycol, a 3 liter ("L") three-necked glass round-bottom flask equipped with an overhead stirrer stirring through the center neck, a reflux condenser and a heating jacket was used. To ensure good mixing, a paddle impeller was used for stirring. A reaction mixture of 551.7 grams ("g") of ethylene glycol and 505.8 g of 1-dodecene was prepared and charged to the reactor at 23°C along with 61 g of powdered catalyst. The impeller stirring rate was set to 400 revolutions per minute ("rpm"). The reactor was heated to 135°C in 30 minutes, maintained at 135°C for 18 hours, and then the reactor was cooled to 23°C by turning off the heater. The reaction mixture was separated into monoethylene glycol and catalyst phases and olefin phases using a separatory funnel.

[0128] The distillation apparatus consisted of a 1-liter round bottom flask connected to a short-path still head with a thermometer connection and a condenser with a vacuum connection at the outlet. The distillation flask was heated in an aluminum block by an IKA heated stirring plate. The combined olefin phases were charged to the distillation pot, which was then stirred and evacuated. Obvious boiling was observed, but no condensate was observed or collected. The temperature of the heating block was increased to 75°C and unreacted dodecane was collected at a distillation head temperature of 25°C to 50°C and a pressure of 13.3 Pascals to 40 Pascals ("Pa"). The temperature of the heating block was gradually increased to 140°C and an intermediate fraction containing both monoether alcohol ethoxylate and dodecene was recovered at a pressure of 13 Pa as the head temperature increased from 50°C to 75°C. C was collected at a head temperature of 70°C to 115°C and a pressure of 6 Pa to 33 Pa. 12 The heating block temperature was gradually increased to 200°C, and at a pressure of 6 Pa, when the head temperature increased from 115°C to 130°C, an intermediate fraction containing both monoether alcohol ethoxylate and diether was collected. The distillation was stopped and the diether retained in the pot was collected. C 12 EO samples to understand the product composition and record it in the results section. 12 The EO is sent to the next sulfation process to prepare sulfate anionic surfactant.

[0129] C 12 Preparation of EO sulfate and ALEO1 sulfate

[0130] All chemical manipulations were performed under a dry nitrogen atmosphere. Before the experiment, all glassware was heated in a laboratory oven to remove residual moisture. A 2L three-necked round-bottom flask was charged with dichloromethane (500 mL) and C 12EO (40g, 0.173mol, 1.0 equivalent). The reaction flask was equipped with an overhead mechanical stirrer, a charging funnel and a thermocouple. Next, chlorosulfonic acid (12.7mL, 0.191mol, 1.1 equivalents) was carefully loaded into the charging funnel. The reaction flask was then immersed in an ice bath and cooled for 20 minutes to 0°C. After the reaction was cooled, chlorosulfonic acid was added dropwise to the reaction flask at a rate of about 1.0mL / min in about 20 minutes. During the addition of chlorosulfonic acid, the reaction temperature did not exceed 5°C. After addition, the reactants were reacted and the temperature was maintained between 0°C and 5°C for 3 hours. At this point, the reaction was neutralized by slowly adding a NaOH aqueous solution (500mL aqueous solution of 18.0gNaOH, 0.9 moles) dropwise. The addition rate was slow enough not to exceed 5°C during the addition process. After adding about 300mL 0.9 molar NaOH solution, the solution became alkaline. The dichloromethane was then carefully removed from the two phase reaction in vacuo. During the dichloromethane removal, a large amount of foaming was observed. After the dichloromethane was removed, the remaining aqueous solution was placed in a freeze dryer / lyophilizer to obtain the secondary alcohol ethoxylate sulfate product, C 12 EO sulfate, as a white solid (61.9 grams). The active content of the secondary alcohol ethoxylate sulfate product was 79.9 wt % as measured by the percent active sulfate content determination method.

[0131] With C 12 The synthesis of ALEO1 sulfate and SA3EO sulfate was carried out in the same manner as EO sulfate.

[0132] C 14 Synthesis of EO

[0133] A 300 mL Parr reactor with a heating jacket and controller was used for the etherification of 1-tetradecene and monoethylene glycol using the catalyst. To ensure good mixing, a paddle impeller was used for stirring.

[0134] A reaction mixture of 100.0 g of monoethylene glycol and 100.0 g of 1-tetradecene was prepared and loaded into a reactor at 23 ° C with 10.0 g of a powdered catalyst. The impeller stirring rate was set to at least 600 rpm. The reactor was heated to 135 ° C in 30 minutes, kept at 135 ° C for 6 hours, and then cooled to room temperature by turning off the heater. The reaction mixture was separated with a separatory funnel. The reaction mixture was separated into monoethylene glycol and catalyst phases and olefin phases using a separatory funnel. 15 batches were produced, and the olefin phases were collected and combined for distillation.

[0135] Use with C 12 The same distillation apparatus used in EO synthesis was used to distill C 14EO. The distillation tank was charged with the product of the olefin phase produced by the operation of multiple batch reactors, then stirred and evacuated. Obvious boiling was observed, but no condensate was observed or collected. The temperature of the heating block was increased to 95°C, and the unreacted 1-tetradecene was collected under the conditions of a distillation head temperature of 30°C to 60°C and a pressure of 27Pa to 5Pa. The temperature of the heating block was gradually increased to 170°C, and at a pressure of 7Pa to 5Pa, when the head temperature was increased from 60°C to 85°C, an intermediate fraction containing both monoether and tetradecene was recovered. C was collected under the conditions of a head temperature of 80°C to 115°C and a pressure of 8Pa to 5Pa. 14 When the temperature of the distillation pot was set to 170°C, the distillation was stopped when no more material was distilled out. Characterization of C by NMR 14 EO samples to understand the product composition.

[0136] C 14 Preparation of EO sulfate

[0137] All chemical manipulations were performed under a dry nitrogen atmosphere. Before the experiment, all glassware was heated in a laboratory oven to remove residual moisture. A 2L three-necked round-bottom flask was charged with dichloromethane (500 mL) and C 14 EO (50g, 0.193mol, 1.0 equivalent). The reaction flask was equipped with an overhead mechanical stirrer, a charging funnel and a thermocouple. Next, chlorosulfonic acid (14.2mL, 0.213mol, 1.1 equivalents) was carefully loaded into the charging funnel. The reaction flask was then immersed in an ice bath and cooled for 20 minutes to 0°C. After the reaction was cooled, chlorosulfonic acid was added dropwise to the reaction flask at a rate of about 1.0mL / min in about 20 minutes. During the addition of chlorosulfonic acid, the reaction temperature did not exceed 5°C. After addition, the reactants were reacted and the temperature was maintained between 0°C and 5°C for 3 hours. At this point, the reaction was neutralized by slowly adding a NaOH aqueous solution (500mL aqueous solution of 18.0gNaOH, 0.9 moles) dropwise. The addition rate was slow enough not to exceed 5°C during the addition process. After adding about 400mL 0.9 molar NaOH solution, the solution became alkaline. The dichloromethane was then carefully removed from the two phase reaction in vacuo. During the removal of DCM, a large amount of foaming was observed. After the DCM was removed, the remaining aqueous solution was placed in a freeze dryer / lyophilizer to obtain the secondary alcohol ethoxylate sulfate product (68.6 grams). The active matter content of the secondary alcohol ethoxylate sulfate product was 87.9 wt%.

[0138] General method for conducting and measuring the amount of dioxane formed during sulfation

[0139] Sulfation was performed using conditions similar to those used to prepare C12EO and C14EO sulfate materials. 400mL to 500mL of dichloromethane and 35 to 50 grams (1 equivalent) of alcohol ethoxylate tested were loaded into a 2L three-necked round-bottom flask. The reaction flask was equipped with an overhead mechanical stirrer, a charging funnel, and a thermocouple. Then, chlorosulfonic acid (1.1 equivalents) was carefully loaded into the charging funnel. The reaction flask was then immersed in an ice bath and cooled for 20 minutes, down to 0°C. After the reaction was cooled, chlorosulfonic acid was added dropwise to the reaction flask at a rate of about 1.0mL / min in about 20 minutes. During the addition of chlorosulfonic acid, the reaction temperature did not exceed 5°C. After addition, the reactants were reacted and the temperature was maintained between 0°C and 5°C for 3 hours. At this point, the reaction was neutralized by slowly dropwise adding a NaOH aqueous solution (18.0g NaOH in 500mL aqueous solution, 0.9M). The addition rate was slow enough not to exceed 5°C during the addition. After neutralization, the two-phase mixture was analyzed by GC to determine the amount of dioxane formed during the sulfation. The crude samples were tightly sealed and stored in a refrigerator until analyzed.

[0140] result

[0141] Alcohol ethoxylate

[0142] The NMR test results are provided in Table 1.

[0143] Table 1

[0144]

[0145] As expected, C 12 EO and C 14 In EO, 95 mol% or more of the oligomers of structure (I) are selected from the group consisting of n and C 12 EO and C 14 5 mol% or less of the oligomers of structure (I) in EO have n of 2 or greater. Specifically, C 12 EO and C 14 In EO, 98 mol% or more of the oligomers of structure (I) are selected from the group consisting of n and C 12 EO and C 14 2 mol% or less of the oligomers of structure (I) in EO have n of 2 or more.

[0146] Table 2 provides the results of the acid digestion tests for the comparative examples ("CE") and the inventive examples ("IE").

[0147] Table 2

[0148]

[0149] In view of the above understanding of the dioxane formation process, it is clear that alcohol ethoxylates in acidic environments (such as H 2 SO 4 The stability of the alcohol ethoxylates (e.g., alcohol ethoxylates with EO content of 2 or more) is very important under acid digestion test conditions. CE1 shows that alcohol ethoxylates with EO content of 2 or more easily generate dioxane under acid digestion test conditions. Under acidic conditions, 2.53 wt% (25,300 ppm) dioxane was observed, and 37% of EO was converted to 1,4-dioxane.

[0150] CE2 has an average of 1 EO, but CE2 contains a large amount of unreacted alcohol and 2 EO adducts (i.e., 0 EO and ≥2 EO, but less than 1 EO). As mentioned above, alcohol ethoxylates with ≥2 EO provide a chemical pathway to form 1,4-dioxane under acidic conditions. Therefore, it is not surprising that CE2 shows 0.35 wt% (3500 ppm) dioxane and 16% EO conversion to 1,4-dioxane. Therefore, if ALEO1 and ALEO2 of CE1 and CE2 are used in products and exposed to sulfuric acid compounds, it is obvious that there will be problems with dioxane regulation.

[0151] C was also tested as IE1 in the acid digestion studies. 12 EO. After acid digestion, the 1,4-dioxane content was 0.00052 wt% (5.2 ppm), which confirms that compositions rich in (i.e., ≥95 mol%) alcohol ethoxylates with 1 EO exhibit better stability under acidic conditions, thereby preventing the formation of 1,4-dioxane. A very small amount of 1,4-dioxane was observed in IE1, probably due to 1 mol% of oligomers of structure (I) with ≥2 EO. It is expected that C 14 EO will provide similarly low dioxane concentrations since it also has only a single EO unit.

[0152] Sulfated surfactants

[0153] Table 3 provides the dioxane measurements for the sulfated surfactants.

[0154] Table 3

[0155]

[0156] a = dioxane was not detected within the limit of 0.1 ppm

[0157] b = dioxane concentration calculated from the average concentration in the aqueous and organic phases at 110°C.

[0158] c = dioxane concentration relative to solids calculated based on average concentration

[0159] d = calculated based on the detection limit (0.1) ppm

[0160] The GC results for CE3 showed that at 110°C, the 3EO sulfate of the secondary alcohol contained 15.3 ppm of dioxane relative to the solids and 2.0 ppm of dioxane in the organic phase, indicating that having ≥2 EO units can cause problems with dioxane. Interestingly, when the inlet temperature was increased to 280°C, the dioxane content of the 3EO sulfate of the secondary alcohol increased significantly, from 2 ppm to 1471 ppm. This result indicates that sulfated surfactants with ≥2 EOs may produce observable dioxane at 110°C, but also indicates that such surfactants may not be stable at high temperatures of 280°C, resulting in the formation of large amounts of dioxane. Similar to CE3, the GC results for CE4 (i.e., sulfated ALEO1) showed that unacceptable amounts of dioxane were formed relative to the solids (i.e., >9 ppm). In addition, CE4 also produced large amounts of dioxane (259 ppm) at 280°C, indicating that CE4 is not stable at high temperatures. IE3 shows a low dioxane content because it contains 95 mol% or more oligomers with 1 EO and 5 mol% or less oligomers with ≥2 EO. Surprisingly, IE3 also shows an extremely low dioxane content and is below the limit of detection (LOD) of the GC and LC methods. Based on the LOD, this indicates that at 110°C, the dioxane content of IE3 is <1.6 ppm relative to the solid. Interestingly, when the inlet temperature is increased to 280°C, the dioxane content of the IE3 material is still less than 1.0 ppm (0.58 ppm). This indicates that C 12 EO not only prevents the formation of dioxane during the sulfation process, but also has a higher thermal stability than the comparative example, which prevents the formation of dioxane.

Claims

1. A method comprising the following steps: Contacting an olefin, an alcohol and a metal silicate catalyst to form an oligomer of an alcohol ethoxylate having structure (I) wherein R1 is an alkyl group, R2 is an alkyl group, and the value of n is 1 to 3; as well as Sulfating the oligomer of structure (I) to form an oligomer of structure (II) wherein R1 is an alkyl group, R2 is selected from the group consisting of alkyl groups, M is selected from the group consisting of a proton, an ammonium cation, a metal cation, a nitrogen cation, a boron cation, a phosphorus cation, triethylamine, triethanolamine, monoethanolamine, and combinations thereof, and n has a value of 1 to 3, wherein n is 1 in 95 mol % or more of the oligomers of structure (II), and n is 2 or greater in 5 mol % or less of the oligomers of structure (II).

2. The process according to claim 1, wherein the olefin is C8 to C 18 An alpha olefin, and the alcohol is monoethylene glycol.

3. The method according to any one of claims 1 and 2, wherein the sum of carbon atoms in R1 and R2 is 7 to 17.

4. The method according to claim 3, wherein the sum of carbon atoms in R1 and R2 is 11 to 13.

5. The method according to any one of claims 1 to 4, wherein the 19, the surface area of ​​the catalyst used to prepare structure (I) is 680m 2 / g.

6. The method according to any one of claims 1 to 5, wherein n is 1 in 98 mol% or more of the oligomers of structure (I), and n is 2 or more in 2 mol% or less of the oligomers of structure (I).

7. A surfactant composition, comprising: Oligomers of surfactants having structure (II) wherein R1 is an alkyl group, R2 is an alkyl group, M is selected from the group consisting of a proton, an ammonium cation, a metal cation, a nitrogen cation, a boron cation, a phosphorus cation, triethylamine, triethanolamine, monoethanolamine, and combinations thereof, and the value of n is 1 to 3, wherein n is 1 in 95 mol % or more of the oligomers of structure (II) in the composition, and n is 2 or greater in 5 mol % or less of the oligomers of structure (II) in the composition.

8. The surfactant composition according to claim 7, wherein R1 of structure (II) is C1 to C 17 Alkyl, R2 is selected from C1 to C 16 The group consisting of alkyl groups, further wherein the total number of carbon atoms in R1 and R2 is 7 to 17.

9. according to the described surfactant composition of one of claim 7 and 8, in wherein said surfactant composition, 98mol% or more of the oligomer of said structure (II) n is 1, and in said surfactant composition, 2mol% or less of the oligomer of said structure (II) n is 2 or greater.

10. The surfactant composition according to claim 7, wherein the sum of carbon atoms in R1 and R2 is 11 to 13.

11. A material comprising: 0.1 wt % to 99.9 wt % of the surfactant composition according to claim 7.